"Ripples of Discontent: Understanding Student Unrest in Vizianagam's Degree Colleges" (International Journal of Food and Nutritional Sciences, 2019)
Student unrest has emerged as a perplexing and nationally significant issue in recent times,drawing attention due to protests, riots, and disruptive behavior among college students. Theprevalence of disorderliness among students poses a fundamental challenge to the successfulexecution of college curricula, necessitating order and discipline for the development of theirpersonalities and a conducive learning environment. However, the roots of this unrest run deepand require careful examination